2019
DOI: 10.1111/jocn.14914
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nursing competence to care for older patients in municipal in‐patient acute care: A qualitative study

Abstract: Aim:To identify critical aspects of nursing competence to care for older patients in the context of municipal in-patient acute care.Background: An increasingly complex and advanced primary healthcare system requires attention to the extent of nursing competence in municipal services. However, competence in complex and advanced care settings must be explored using perspectives which acknowledge the complexity of nurses' performance.Design: A phenomenological hermeneutic, qualitative approach with individual ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Emergency nursing 0 (0-1) 1 (0-1.75) 0 (0-1) 0 (0-2) 0 (0-1) 0 (0-1) 0 (0-1) 0 (0-1) 0 (0-1) acknowledged and supported by a professional leadership [8,11,43] The benefits of having collegial support to handle the workload is described in several studies [5,42,44]. This includes, among other things, to assess and discuss patients and different situations in order to make accurate decisions and interventions, as well as access to qualified second opinions [5,42,44].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Emergency nursing 0 (0-1) 1 (0-1.75) 0 (0-1) 0 (0-2) 0 (0-1) 0 (0-1) 0 (0-1) 0 (0-1) 0 (0-1) acknowledged and supported by a professional leadership [8,11,43] The benefits of having collegial support to handle the workload is described in several studies [5,42,44]. This includes, among other things, to assess and discuss patients and different situations in order to make accurate decisions and interventions, as well as access to qualified second opinions [5,42,44].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was based on a previous qualitative study which explored critical aspects of nursing competence to care for older patients in MipACs in Norway [11]. That study revealed the importance of professional nurses in the staff, holding advanced competence, particularly within specialisation in emergency, geriatric and psychiatric nursing in these units.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations